Effects of fermented bamboo fiber on intestinal health and fecal pollutants in weaned piglets - Jia, Yubiao; Huang, Qiuming; Song, Rui; Tang, Yanling; Feng, Mengxin; Lu, Jianjun (Frontiers in Nutrition, 2025)
IntroductionWeaning stress adversely affects piglet growth and development, thereby reducing the economic efficiency of pig farming operations. Furthermore, pig feces are a major source of environmental pollution, underscoring the need for effective strategies to mitigate fecal output at its source.MethodsThis study investigated the effects of dietary supplementation with fermented bamboo fiber (FBF) on growth performance, intestinal barrier integrity, gut microbiota composition, and fecal pollutant levels in weaned piglets. A total of 144 Duroc × Landrace × Yorkshire piglets, weaned at 21 days of age, were randomly assigned to 4 groups, with six replicates per group and 6 piglets per replicate. The control group (CON) received a basal diet, while the three treatment groups were fed the basal diet supplemented with 1, 1.5, and 2% FBF, respectively. The trial lasted 30 days.ResultsThe findings revealed that FBF supplementation fortified the intestinal barrier, modulated colonic microbial communities, and decreased fecal pollutant levels. Among the treatment groups, supplementation with 1.5% FBF produced the most significant improvements in piglets’ growth performance and intestinal barrier function, as well as the strongest microbial interactions and the greatest reduction in fecal pollutants.DiscussionThese results suggest that FBF supplementation can alleviate weaning stress and mitigate the environmental impact of pig feces, with 1.5% identified as the optimal supplementation level.